Bcl‐3 suppresses differentiation of RORγt+ regulatory T cells. Issue 6 (23rd February 2021) - Tang, Wanhu; Saret, Sun; Tian, Ruxiao; Wang, Hongshan; Claudio, Estefania; Murphy, Philip M; Siebenlist, Ulrich
Abstract: Regulatory T cells (Tregs) exert inhibitory function under various physiological conditions and adopt diverse characteristics following environmental cues. Multiple subsets of Tregs expressing master transcription factors of helper T cells such as RORγt, T‐bet, Gata3 and PPARγ have been characterized, but the molecular mechanism governing the differentiation of these subsets remains largely unknown. Here we report that the atypical IκB protein family member Bcl‐3 suppresses RORγt + Treg accumulation. The suppressive effect of Bcl‐3 was particularly evident in the mouse immune tolerance model of anti‐CD3 therapy. Using conditional knockout mice, we illustrate that loss of Bcl‐3 specifically in Tregs was sufficient to boost RORγt + Treg formation and resistance of mice to dextran sulfate sodium‐induced colitis. We further demonstrate the suppressive effect of Bcl‐3 on RORγt + Treg differentiation in vitro . Our results reveal a novel role of nuclear factor‐kappa B signaling pathways in Treg subset differentiation that may have clinical implications in immunotherapy. Abstract : Here we report that the atypical IκB protein family member Bcl‐3 suppresses RORγt + regulatory T‐cell (Treg) accumulation. The suppressive effect of Bcl‐3 was particularly evident in the mouse immune tolerance model of anti‐CD3 therapy. Loss of Bcl‐3 in Tregs was sufficient to boost RORγt + Tregs formation and resistance of mice to dextran sulfate sodium‐induced colitis.